Efficacy of electrical stimulation of the zygomaticus muscle in complete facial paralysis: evidence from facial grading and automated image analysis - Johannes Krauß; Gabriel Meincke; Maren Geitner; Anna-Maria Kuttenreich; Jan Beckmann; Dirk Arnold; Jonas Ballmaier; Thomas Lehmann; Winfried Mayr; Orlando Guntinas-Lichius; Gerd Fabian Volk (European Journal of Translational Myology)
Surface Functional Electrical Stimulation (FES) is a well-studied intervention for multiple muscular disorders. However, it is still controversially discussed as a complementary therapy for complete facial paralysis. The aim of this intervention is to test a daily home-based ES concept as a pilot study regarding safety, feasibility, and effects on facial functionality and symmetry. In a prospective single-centre pilot study, 10 patients (median 61 years, denervation 130 d) with complete peripheral facial paralysis performed home-based FES of the affected lateral mouth region Stimulation parameters, facial paralysis scores and standardised photographs were assessed in monthly follow-ups. No serious adverse events appeared. Stimulation parameters could be constantly increased indicating effective muscle training while subjectively perceived functionality of the face improved. Thus, smile angle of the paralysed side improved as well. FES is a safe therapy model for application in facial nerve paralysis patients. A feasible stimulation protocol could be applied, which improved the functionality and symmetry of the stimulated facial region. A future controlled, randomised and double-blind follow-up study is needed to investigate these initial results in a further evolved replicable setting.